IMPLEMENTASI TEKNOLOGI PEMBELAJARAN DAN PENGARUHNYA TERHADAP MUTU PENDIDIKAN DI IAI HASANUDDIN PARE KEDIRI - Miftaahul Ilma, Devi Mirza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology requires universities to adapt to improve the quality of education, including in Islamic Religious Education (PAI) learning. Howeveir, the implementation of learning technology has not been fully optimized due to limited infrastructure, differences in digital literacy between lecturers and students, and the continued use of conventional methods. This study aims to describe the implementation of learning technology and analyze the suipporting factors, obstacles, and their influence on educational quality at the Hasanuddin Islamic Institute (IAIH) in Pare, Kediri. The study used a descriptive qualitative approach, with data collection techniqueis through interviews, observation, and documentation. The results indicate that the use of a Learning Management System (LMS) and digital learning media has a positive impact on learning effectiveness, academic interaction, and student access to learning resources, particularly in PAI leiarning.